Symbiotic hollow fiber membrane photobioreactor for microalgal growth and bacterial wastewater treatment. (November 2016) - Vu, Linh T.K.; Loh, Kai-Chee
Highlights: Hollow fiber membrane photobioreactor developed for photosynthetic aeration. Established symbiotic relationship between microalgae and bacteria. Biodegradation of 500 mg/L glucose using oxygen from microalgae only. Effects of flow orientation and membrane surface area studied. Abstract: A hollow fiber membrane photobioreactor (HFMP) for microalgal growth and bacterial wastewater treatment was developed. C. vulgaris culture was circulated through one side of the HFMP and P. putida culture was circulated through the other. A symbiotic relationship was demonstrated as reflected by the photo-autotrophic growth of C. vulgaris using CO2 provided by P. putida and biodegradation of 500 mg/L glucose by P. putida utilizing photosynthetic O2 produced by C. vulgaris . Performance of the HFMP was significantly enhanced when the microalgal culture was circulated through the lumen side of the HFMP: the average percentage of glucose degraded per 8-h cycle was as high as 98% and microalgal biomass productivity was increased by 69% compared to the reversed orientation. Enhanced glucose biodegradation was achieved in an HFMP packed with more fibers indicating the easy scalability of the HFMP for increased wastewater treatment efficiency.